The Effectiveness of the METAL GEGANA Media in ETH Method Towards the Learning Outcomes of SDN Soka 01 - Aida Belinastuti; Mei Fita Asri; Prasena Arisyanto (LPPM Universitas Buana Perjungan Karawang, 2020)
The purpose of this study was to determine the Effectiveness of Digital Media Animation of Disaster Mitigation (METAL GEGANA) in the ETH method on the theme Theme 5 Ecosystem Subtema 1 Ecosystem Component on student learning outcomes in fifth grade SD N Soka 01 Magelang Regency. This research was conducted by taking the subjects of elementary school students Soka 01 Magelang District class 5 with a total of 26 students. This research used a quantitative approach using the One-Group pretest-posttest Design research design. Data collection techniques based on observations and tests of learning outcomes. The results of the analysis using the t test results obtained tcount of 6.734727471 and ttable of 2.0189 with a level of 5% (tcount> t table). An increase in the average posttest result was 75.3. This is evidenced by the value of students who reach KKM 70 as many as 17 students completed with the highest value of 95 while students who have not reached KKM as many as 9 students with the lowest value of 50. Therefore it can be concluded that the animation video media METAL GEGANA is effective in the ETH method on the learning outcomes of the fifth grade theme 5 SD N Soka 01 Magelang Regency.